Microstamped Petri dishes for scanning electrochemical microscopy analysis of arrays of microtissues. - Adithya Sridhar (Public Library of Science (PLoS), 2014)
While scanning electrochemical microscopy (SECM) is a powerful technique for non-invasive analysis of cells, SECM-based assays remain scarce and have been mainly limited so far to single cells, which is mostly due to the absence of suitable platform for experimentation on 3D cellular aggregates or microtissues. Here, we report stamping of a Petri dish with a microwell array for large-scale production of microtissues followed by their in situ analysis using SECM. The platform is realized by hot embossing arrays of microwells (200 μm depth; 400 μm diameter) in commercially available Petri dishes, using a PDMS stamp. Microtissues form spontaneously in the microwells, which is demonstrated here using various cell lines (e.g., HeLa, C2C12, HepG2 and MCF-7). Next, the respiratory activity of live HeLa microtissues is assessed by monitoring the oxygen reduction current in constant height mode and at various distances above the platform surface. Typically, at a 40 μm distance from the microtissue, a 30% decrease in the oxygen reduction current is measured, while above 250 μm, no influence of the presence of the microtissues is detected. After exposure to a model drug (50% ethanol), no such changes in oxygen concentration are found at any height in solution, which reflects that microtissues are not viable anymore. This is furthermore confirmed using conventional live/dead fluorescent stains. This live/dead assay demonstrates the capability of the proposed approach combining SECM and microtissue arrays formed in a stamped Petri dish for conducting cellular assays in a non-invasive way on 3D cellular models.